1997
DOI: 10.1111/j.1467-8624.1997.tb01938.x
|View full text |Cite
|
Sign up to set email alerts
|

Language and Williams Syndrome: How Intact Is "Intact"?

Abstract: It has been claimed that Williams syndrome (WS), a rare neurodevelopmental disorder, is characterized by serious cognitive deficits alongside intact language. The syndrome is often used as a prime example of the modularity of an innate faculty for morphosyntactic rules. We challenge this claim and hypothesize that morphosyntax, although surprisingly good given WS level of mental retardation, is by no means intact. We make an initial test of this hypothesis through an analysis of the receptive language of a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
3
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 34 publications
7
108
3
3
Order By: Relevance
“…3 Language delay is usually present, but verbal IQ is generally, although not always, higher than performance IQ in WBS cases. [3][4][5][6][7][8] By contrast, although language delay is common to both disorders, subjects with autism tend to have higher performance IQs than verbal IQs and display excessive social versus non-social anxiety. However, difficulty reading emotions from the face and voice, an inability to get along with peers and poor social judgement are common features of both disorders.…”
mentioning
confidence: 99%
“…3 Language delay is usually present, but verbal IQ is generally, although not always, higher than performance IQ in WBS cases. [3][4][5][6][7][8] By contrast, although language delay is common to both disorders, subjects with autism tend to have higher performance IQs than verbal IQs and display excessive social versus non-social anxiety. However, difficulty reading emotions from the face and voice, an inability to get along with peers and poor social judgement are common features of both disorders.…”
mentioning
confidence: 99%
“…Problems with gender agreement in other atypical populations have been attributed to the fact that the inflected elements are distributed across several words within a noun phrase (cf. Karmiloff-Smith et al, 1997;Orgassa and Weerman, 2008), for example, den store bilen 'the big car', where the agreeing elements are the determiner den, the inflection -e on the adjective store and the inflection -en on bilen, all exponents of masculine gender in Norwegian. One challenge with gender agreement for individuals with limitations in verbalauditory processing is to extract and internalize general information about these distributed patterns from exemplars.…”
Section: Discussionmentioning
confidence: 99%
“…Nominal domain studies have shown that grammatical gender is a problem for children with SLI (Roulet-Amiot and Jakubowicz, 2006; Orgassa and Weerman, 2008) and with Williams syndrome (Karmiloff-Smith, Grant, Berthoud, Davies, Howlin, and Udwin, 1997). In summary, there are commonalities as well as differences in morphological impairment across types of impairment, across structures and across languages.…”
Section: Development Of Morphological Skills In Atypically Developingmentioning
confidence: 93%
“…Individuals with Williams syndrome additionally display a relatively predictable and consistent cognitive and behavioral phenotype, including global reductions in total IQ, particularly with respect to visuospatial intelligence [Meyer-Lindenberg et al, 2006]. Curiously, individuals with Williams syndrome have been shown to demonstrate linguistic capacity characterized by elaborated vocabulary and unusually expressive use of phrases [Udwin and Yule, 2005; Reilly et al, 2004], but struggle with elements of syntax, grammatical structure, and embedded meaning [Karmiloff-Smith et al, 1997; Brock, 2007]. Among the most salient features of Williams syndrome, affected individuals tend to show an abnormally high drive to engage in social and affiliative behavior, and exhibit an unusual willingness to approach strangers [Doyle et al, 2004; Järvinen-Pasley et al, 2008].…”
Section: Modeling Human Evolution Through Genetic Disorders: the Casementioning
confidence: 99%
“…Deficits in sentence morphology and syntax [Karmiloff-Smith et al, 1997] indicate difficulty in encoding rules of proper language use and grammatical structure [Thomas and Karmiloff-Smith, 2005; Clahsen, 1998]. Given the role of the striatum in recursive elements and rule-encoding in language use and acquisition [Teichmann et al, 2006] these processing abnormalities might be related to differences in striatal microstructure.…”
Section: Modeling Human Evolution Through Genetic Disorders: the Casementioning
confidence: 99%